Procedural characteristics and outcomes following chronic total occlusion coronary intervention: pooled analysis from 5 registries. (3rd October 2021) - Rathore, Sudhir; Khanra, Dibbendu; Galassi, Alfredo R; Boukhris, Marouane; Tsuchikane, Etsuo; Dens, Joseph; Mashayekhi, Kambis; Grantham, J Aaron; Brilakis, Emmanouil S.; Karmpaliotis, Dimitri; Werner, Gerald S.
ABSTRACT: Background: Recent improvements in clinical skills, technology, and hardware have resulted in improved success rates with chronic total occlusion (CTO) percutaneous coronary intervention (PCI). We performed a study level pooled analysis from the five largest registries of percutaneous coronary intervention (PCI) of CTO. Research design and methods: We conducted pooled analysis of 9500 patients in registries and data on procedural characteristics, technical success, and MACCE was collected. Results: A total of 9500 patients were included in the analysis. Mean age was 65.4 years with previous CABG in 24.8%, reattempt procedure in 24.8% and mean JCTO score was 2.2. Final wiring strategy in hybrid algorithm-based registries was AWE in 40.8–58%, Retrograde in 24–35%, ADR in 16–25% and in Expert JCTO and EURO CTO was AWE in 72–75% and retrograde in 25–28%. Technical success was achieved in 87.8%. In hospital MACCE was 2.5% (95% CI: 1.8– 3.4%), mortality 0.44% (95% CI: 0.23–0.84%), stroke 0.2% (95% CI: 0.1–0.3%); myocardial infraction 1.6% (95% CI: 1.1–2.2%); and cardiac tamponade 0.8% (95% CI: 0.5 to 1.3%). Conclusion: CTO PCI is currently performed with high technical success rates and low complication rates in experienced hands utilizing various techniques.